Characteristics of the Waviness End-Face Mechanical Seal in Reactor Coolant Pump Considering the Viscosity-Temperature Effect - Ma, Yu; Wang, Ya-Hui; Zhou, Hai-Chun; Su, Wen-Tao (Frontiers in Energy Research, 2021)
This work studies the main performances of the waviness end-face mechanical seal with considering the fluid flow and thermal effect. The coupled thermal-hydraulics process is simulated using the OpenFOAM based on the coupled Navier-Stokes equation and energy balance equation to analyze the performance of mechanical seal. The viscosity-temperature effect of the sealing medium is considered in the heat-flow coupling due to the characteristics of the working fluid. Under different conditions, the effect of the viscosity-temperature effect is analyzed by comparing it with the non-viscous fluid. Solutions of numerical simulations show that the viscosity-temperature effect may increase the leakage while decrease the opening force and the liquid film stiffness. In particular, when considering the viscosity-temperature effect, the values of liquid film stiffness may have a negative value. All these properties indicate that the viscosity-temperature effect is bad for the stable operation of the mechanical seal. However, from the perspective of liquid film temperature rise, the viscosity-temperature effect may reduce the temperature rise in the liquid film, which improves the safety of the mechanical seal in some aspects. Therefore, through comprehensive analysis, when designing the waviness mechanical seal, the optimal structural parameters can be set as hi=2.5μm, β=900μrad, (Rd-Ri)/(Ro-Ri)=0.2, α=0.8, and k=9.